The arena of natural resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Politics, property and production in the West African Sahel. Understanding natural resources management Edited by T A Benjaminsen & C Lund, Nordic Africa Institute, Sweden, 2001. 335 pp. ISBN 91 7106 476 1 SEK 280 Euro 31.05